2010
DOI: 10.1002/chem.201002076
|View full text |Cite
|
Sign up to set email alerts
|

Rotaxanes Capable of Recognising Chloride in Aqueous Media

Abstract: A new, versatile chloride-anion-templating synthetic pathway is exploited for the preparation of a series of eight new [2]rotaxane host molecules, including the first sulfonamide interlocked system. (1)H NMR spectroscopic titration investigations demonstrate the rotaxanes' capability to selectively recognise the chloride anion in competitive aqueous solvent media. The interlocked host's halide binding affinity can be further enhanced and tuned through the attachment of electron-withdrawing substituents and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 86 publications
3
56
0
Order By: Relevance
“…Indeed, this hypothesis is supported by molecular dynamics calculations (see below) and similar 1 H NMR chemical shift trends were observed for related rotaxane host systems 28. 40, 41 …”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, this hypothesis is supported by molecular dynamics calculations (see below) and similar 1 H NMR chemical shift trends were observed for related rotaxane host systems 28. 40, 41 …”
Section: Resultssupporting
confidence: 67%
“…All four anion complexes exhibit an orthogonal interlocked co‐conformation commonly observed for related rotaxane hosts 40. 55 This structure is illustrated in Figure 8 with a selected snapshot taken from a MD run of the iodide complex.…”
Section: Resultsmentioning
confidence: 87%
“…[13,14] By employing different anion-binding motifs within the components of rotaxanes, a variety of selective interlocked host systems for chloride, bromide, and iodide anions have been prepared containing pyridinium, [15] triazolium, [16] and iodotriazolium [17] axle motifs, respectively. However, while the imidazolium group has been exploited in the assembly of a number of pseudorotaxanes [18][19][20] and recent bis-and tetra-imidazolium rotaxane systems, [21] to the best of our knowledge no mono-imidazolium interlocked structures have been synthesized, either for anion recognition or in others area of supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions of 17·Cl with diamine 30 (n=1) or 30 (n=0) and appropriate bis(acid chloride) yielded two series of [2]rotaxanes, 33-35 and 36-38, respectively (Scheme 9). 72 For example, the reaction of 17·Cl with diamine 30 (n=1) and 3,5-bis(chlorocarbonyl)pyridine afforded rotaxane 34·Cl. This compound upon treatment with NH 4 PF 6 was converted into 34·PF 6 which by methylation afforded the dicationic [2]rotaxane 39·I·PF 6 .…”
Section: Example Bmentioning
confidence: 99%
“…It was observed that in the case of 17·Cl used as a thread, the yield was higher than in the case of 17·PF 6 ; this fact indicates that chloride as a templating agent considerably enhances the rotaxane synthesis. 72 For investigation of anion-binding properties of rotaxanes, the exchange of the chloride templating anion for the non-coordinating PF 6 ‾ was necessary.The anion-binding properties of rotaxanes (33)(34)(35)(36)(37)(38) . .…”
Section: Example Bmentioning
confidence: 99%